Divergence of flowering-related genes to control flowering in five Euphorbiaceae genomes - Jiang, Lan; Fan, Tingting; Wang, Lihu; Zhang, Lin; Xu, Jun (Frontiers in Plant Science, 2022)
The Euphorbiaceae species, including castor bean (Ricinus communis), physic nut (Jatropha curcas), tung tree (Vernicia fordii), cassava (Manihot esculenta), and rubber tree (Hevea brasiliensis), have important economic values because they are raw materials for the production of biodiesel and rubber, etc. However, reproductive growth may lead to lower yields. The flowering mechanisms are still excluded in the Euphorbiaceae species. The flowering-related genes of Arabidopsis thaliana (Arabidopsis) were used as a reference to determine the orthologs of these genes in Euphorbiaceae genomes. These identified genes were clustered into seven pathways, such as gibberellins, floral meristem identity (FMI), vernalization, photoperiod, floral pathway integrators (FPIs), and autonomous pathways. Then, some key numbers of flowering-related genes are widely conserved in the Euphorbiaceae genomes, such as FPI genes LFY, SOC1, and FT, as well as FMI genes AG, CAL, and FUL. However, some genes, including FRI, FLC, and GO, were missing in several or all five Euphorbiaceae species. In this study, we proposed the putative mechanisms of flowering-related genes to control flowering and provided new candidate flowering genes for using marker-assisted breeding to improve variety quality.